THE RELATIONSHIP OF WORK STRESS, EMOTIONAL INTELLIGENCE, AND THE PERFORMANCE OF STAFF IN THE OFFICE OF THE MINISTRY OF RELIGION BATAM CITY INDONESIA - Hazriyanto, Indra Firdiyansyah,Syed Sofian Syed Salim (International Conference on Industrial Revolution for Polytechnic Education, 2019)
Issues that generally are facing is how can create human resources capable of generating optimal performance so that the objectives of the organization can be achieved. Many factors can affect the performance of the person who will ultimately be able to realize the achievement of organizational performance. Problem in the work stress, emotional intelligence, and performance becomes important to note. The variables examined in this study are work stress, emotional intelligence, and the performance of staff in the Office of the Ministry of Religion Batam city. The data collection tool in research using questionnaires and in analysis with SPSS statistics tools. This assessment involves 13 items of work stress, there are 28 items of emotional intelligence, and 6 items of performance. Populations and samples in this study was 33 staff as respondent. The acquired results of the research show that the stress of work and the performance has a negative and significant relationship, emotional intelligence and performance had a positive and significant relationship, whereas sters work and emotional intelligence competencies the negative is not significant. For upcoming research suggested examining the demographic and other variables that are not examined in this study such as; commitment, and job satisfaction.